Lipid composition and some bioactivities of 3 newly isolated microalgae (Tetraselmis sp. IMP3, Tetraselmis sp. CTP4, and Skeletonema sp.) - Cardoso, Cátia (2020)
Recently isolated microalgae Tetraselmis sp. IMP3, Tetraselmis sp. CTP4, and Skeletonema sp. were studied. The three novel strains contained relatively high levels of polyunsaturated fatty acids (PUFA) and n3 PUFA. However, highly unsaturated n3 FA contents were relatively low (5.7-13.0% of the total FA). In general, eicosapentaenoic acid (EPA, 20:5 n3) contents were low (< 6.4% of the total FA). However, in Skeletonema biomass, EPA levels were higher than 10% of the total FA. alpha-Linolenic acid (ALA, 18:3 n3) and 16:3 n4 were the main PUFA in Tetraselmis strains and Skeletonema, respectively. High contents of myristic (14:0) and palmitoleic (16:1 n7) acids were found in Skeletonema (exceeding 20% of the total FA in both cases), whereas the Tetraselmis strains were rich in palmitic (16:0), 15-27% of the total FA, and oleic (18:1 n9) acids, 12-19% of the total FA. Linoleic acid (18:2 n6) content was low in Skeletonema (< 1% of the total FA). This microalga had the highest total polyphenol content, reaching 300-400 mg/100 g dw. Gentisic acid was the main phenolic compound in the aqueous and ethanolic extracts of this microalga. The highest antioxidant activity was displayed by Skeletonema. The ferric ion reducing antioxidant power (FRAP) and 2,2 '-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) methods showed higher antioxidant power for Skeletonema sp. extracts, reaching an ABTS reduction of more than 80%. Concerning anti-inflammatory activity, ethanolic extracts of Skeletonema sp. exhibited the highest inhibitory capacity of cyclooxygenase-2 (COX-2), 82 +/- 2%, which compares to 36 +/- 9% in Tetraselmis sp. CTP4 and 45 +/- 5% in Tetraselmis sp. IMP3. Aqueous extracts had always a lower anti-inflammatory capacity, 6-30%. Therefore, these microalgae have potential for multiple applications, ranging from bioactive feedstocks to aquaculture and nutraceutical uses.